Bibliometric analysis of nutrition in gastric cancer from 2013 to 2023 - Li, Ruyin; Zhao, Zirui; Huang, Hongyun; Yu, Jianchun (Frontiers in Nutrition, 2024)
Background: Increasing evidence suggests that nutrition plays an important role in the treatment of gastric cancer. However, no bibliometrics analysis has been conducted in this field. Our study aimed to conduct a bibliometric study to explore the latest publishing trends and areas of intense activity within the sphere of nutrition in gastric cancer. Method: Publications were extracted from the Web of Science Core Collection. CiteSpace (Version 6.2.4) and VOSViewer (Version 1.6.18)were used for visual analysis. Results: In total, there were 441 publications authored by 2941 authors from 809 organizations and 47 countries, published in 182 journals from 2013 to 2023. The most prolific country was China, and the most productive institution was Chinese Academy of Medical Sciences. The most leading core journal was Nutrients. P Daisuke Kobayashi and Yasuhiro Kodera were the most influential authors. The first highly cited document was published in Gastric Cancerby Kamarajah et al. The hotspots in this field were nutrition treatment and nutritional status. Moreover, research of nutritional status and nutrition-related prognosis in gastric cancer might be a potential trend. Conclusion: Nutrition in gastric cancer is a burgeoning research field garnering increasing attention. Further investigation is necessary to better understand the impact of nutritional status on the prognosis of gastric cancer.